2006
DOI: 10.1007/s10637-006-5937-2
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study of amrubicin, 9-amino-anthracycline, in patients with advanced non-small-cell lung cancer (Study 1): West Japan Thoracic Oncology Group (WJTOG) trial

Abstract: Amrubicin was an active, well-tolerated agent in the treatment of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
1
31
2
Order By: Relevance
“…Therefore, we decided to investigate the predictive factors associated with grade 3–4 (<1,000 and ≥500/mm 3 ) rather than grade 4 (<500/mm 3 ) neutropenia in the present study. In this study, the incidence of grade 3–4 neutropenia was 62% (38/61), which was a little lower than that in previous phase II studies (median 78%; range 39–97%) [4,5,6,7,8,9,10,11,12,13,14]. Multivariate logistic analysis revealed that higher doses of AMR, female gender, and lower baseline hematocrit values were significant predictors of grade 3–4 neutropenia in patients with lung cancer treated with AMR monotherapy.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Therefore, we decided to investigate the predictive factors associated with grade 3–4 (<1,000 and ≥500/mm 3 ) rather than grade 4 (<500/mm 3 ) neutropenia in the present study. In this study, the incidence of grade 3–4 neutropenia was 62% (38/61), which was a little lower than that in previous phase II studies (median 78%; range 39–97%) [4,5,6,7,8,9,10,11,12,13,14]. Multivariate logistic analysis revealed that higher doses of AMR, female gender, and lower baseline hematocrit values were significant predictors of grade 3–4 neutropenia in patients with lung cancer treated with AMR monotherapy.…”
Section: Discussioncontrasting
confidence: 67%
“…In phase II trials of second- or third-line AMR monotherapy for the treatment of SCLC, the response rates and the overall survival were 21–53% and 6–12 months, respectively [4,5,6,7,8,9,10,11]. In the treatment of NSCLC, the response rates of AMR monotherapy were 12–28% [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Amrubicin chemotherapy was discontinued in all ILD cases; 1 case improved spontaneously, while it was improved after corticosteroid treatment in the other 2 cases. Although ILDrelated deaths have been reported in some of the amrubicin clinical trials (2,5,11,13), the outcome of amrubicin-associated ILD was good in each of our cases. In our study, the ILD group tended to show a poor PS, a higher smoking index and contained a higher proportion of patients with pulmonary emphysema and preexisting pulmonary fibrosis in comparison to the non-ILD group.…”
Section: Discussionmentioning
confidence: 49%
“…The patients of these three cases had asymptomatic interstitial pneumonitis prior to chemotherapy. As a result, the protocol was revised during the trial to exclude the patients who had confirmed or suspected interstitial pneumonitis at baseline (2). In Japan, the package insert of amrubicin warns physicians that it should not be used for patients with symptomatic and chest X-ray-evident interstitial pneumonitis.…”
Section: Introductionmentioning
confidence: 99%
“…Two phase II studies of amrubicin in patients with previously untreated advanced NSCLC demonstrated in succession an overall response rate of 27.9 and 18.3%, respectively, and a median survival time (MST) of 9.8 months and 8.2 months, respectively [14,15]. This showed that amrubicin is equivalent to newer agents such as taxanes, gemcitabine, vinorelbine and pemetrexed in terms of single-agent activity against NSCLC.…”
Section: Introductionmentioning
confidence: 99%